Freedom as Non-Domination: P. Pettit’s Republican Ideal of Citizenship - Žutautaitė, Elžbieta (Problemos, 2025)
The constantly changing political circumstances and the expanding structure of civic society forces to search for an alternative to the theory of liberalism whose principles are incapable of mobilizing different groups of citizens for active participation. Moreover, the increasing dissatisfaction in government authorities calls for a solution to contain citizens’ emotions and promote a dialogue. The paper argues that Philip Pettit’s republican theory of freedom as non-domination is a valid alternative to liberalism to empower citizens for political action. The reason for this is that republican theory focuses on the protection of free agency, the virtue of vigilance encourages observation of political life and, if necessary, the opportunity to get involved, and the principle of non-domination itself imposes an obligation to ensure social justice. However, non-domination theory cannot address the problem of societal fragmentation because it assumes that the citizen is a rational agent and does not search for ways to persuade opposing groups to engage in a dialogue.